Insecticide chlorfenapyr confers induced toxicity in human cells through mitochondria-dependent pathways of apoptosis - Longfei Wang; Zheng Qu; Yifan Xu; Guangqing Yu; Xiangyang Liu; Meizi Wang; Shiheng An; Xinming Yin; Risong Na; Youwu Hao (Ecotoxicology and Environmental Safety)
Pesticides are always used in the environment, the unexpected effects of pesticides on the environment and non-target organisms need to be continuously studied. Insecticide chlorfenapyr (Chl) is widely used in agriculture and also recommended for public health use (e.g., providing protection from malaria). Here we study toxic effects of Chl on human alveolar carcinoma cells (A549) and human normal liver cells (L02) in vitro. Chl's ability to induce DNA damage and apoptosis in human cells was confirmed through alkaline comet assay, immunofluorescence assay, and flow cytometric analysis. Further research showed that Chl induced mitochondrial damage (the collapse of mitochondrial membrane potential and the opening of mitochondrial permeability transition pore) with up-regulated expression of Bax/Bcl-2 leads to the release of cytochrome c from mitochondria which in turn activated the apoptotic pathway. Meanwhile, the key protein PARP is cleaved during apoptosis, resulting in the inhibition of DNA damage repair. In short, human A549 and L02 cells exposed to Chl were experiencing DNA damage and apoptosis linked to mitochondria. The results of this study supply theoretical understanding of Chl's toxicity on human cells, and can attract attention on the potential threat of insecticide Chl to human health.